Impact of Clinical Decision Support on Time to Order Resolution for Patients with Documented Allergies - Tenielle Watkins; Sandra M. Aguero; Michael Jaecks (MDPI AG, 2018)
Failure to appropriately document patient medical information, such as allergies, is an important cause of medication errors. Lack of allergy details in the electronic medical record (EMR) may prolong the pharmacist order verification process. A retrospective chart review was conducted in October 2017, to evaluate the impact of incomplete allergy details on time to antibiotic order resolution at the Einstein Medical Center Philadelphia. Details were present on 71% of orders. The difference in median time to order resolution, for orders with versus without details, was –21 min (95% CI (confidence interval), –39 to –2.9; p = 0.02). The difference in median time to order resolution for orders, based on pharmacist work shift was, –21 min for the first shift (95% CI, –41.2 to –0.8; p = 0.04), –50 min for the second shift (95% CI, –109.8 to 9.8; p = 0.10), and +3 min for the third shift (95% CI, –36.1 to 30.1; p = 0.85). Orders with an allergy intervention by a pharmacist were 2.75 times more likely (adjusted odds ratio = 2.75; 95% CI, 0.98 to 7.7; p = 0.06) to have a therapy change than orders without allergy interventions. Based on the results, when information about antibiotic allergies lacks details, it takes more time for pharmacists to resolve alerted orders.